2005
DOI: 10.3354/meps298101
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen load and irradiance affect morphology, photosynthesis and growth of Caulerpa prolifera (Bryopsidales: Chlorophyta)

Abstract: The effect of nitrogen (N) load and irradiance on morphology, growth and photosynthetic performance was studied in the green macroalga Caulerpa prolifera (Forsskål) J. V. Lamouroux from the Gulf of Cádiz (south Spain). Constant growth rates were obtained for thalli growing at different N loads, which could be fitted to tissue N using the Droop equation, rendering a maximum growth rate of 0.09 d -1 , a minimum tissue N level of 1.71% dry weight (DW) and a critical tissue N of 5.2% DW. N limitation had no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Although growth saturation with increasing tissue N has never been defined in C. cylindracea, values of tissue N content in our study were similar to the critical values reported for some nitrophilic opportunistic macroalgae (Lavery & McComb, 1991), suggesting that, like non-invasive Caulerpa spp., C. cylindracea is a nitrophilic species (Malta et al, 2005). Nutrient enrichment in laboratory culture systems confirmed the general high affinity for N of the C. racemosa-peltata complex (Belton et al, 2014), which may correspond to strongly nitrophilous behaviour (Table 3; Larned, 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Although growth saturation with increasing tissue N has never been defined in C. cylindracea, values of tissue N content in our study were similar to the critical values reported for some nitrophilic opportunistic macroalgae (Lavery & McComb, 1991), suggesting that, like non-invasive Caulerpa spp., C. cylindracea is a nitrophilic species (Malta et al, 2005). Nutrient enrichment in laboratory culture systems confirmed the general high affinity for N of the C. racemosa-peltata complex (Belton et al, 2014), which may correspond to strongly nitrophilous behaviour (Table 3; Larned, 1998).…”
Section: Discussionmentioning
confidence: 82%
“…A few studies provide reliable data about photosynthesis (Beer et al, 1998;Enríquez et al, 2004;Malta et al, 2005;Olesen et al, 2002;Silva and Santos, 2003;Terrados and Ros, 1991, and others on pigment composition (Casazza and Mazzella, 2002;Hegazi et al, 1998Hegazi et al, , 2000 and salinity adaptation (Fernández-Torquemada and Sánchez-Lizaso, 2011;Pagès et al, 2010;Sandoval-Gil et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…This result is similar to that of a study comparing the photo-physiology of both macrophytes within a Mediterranean coastal lagoon (García-Sánchez et al 2012). This outcome has implications in the way light is absorbed by both macrophytes, as well as in the quantity and quality of pigment contents, and in ways to ameliorate/dissipate the excess of light energy reaching photosynthetic tissues (Malta et al 2005, García-Sánchez et al 2012. Our results demonstrated that the seagrass C. nodosa has a consistently larger optimum quantum yield (F v /F m ), ETR max and photosynthetic efficiency than the green alga C. prolifera, particularly when PAR values are larger (May in comparison with February 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the Mar Menor (Mediterranean Sea), C. nodosa is mainly restricted to shallow-water areas (<1 m), while slightly deeper areas (2-5 m) are dominated by mono specific meadows of C. prolifera (García-Sánchez et al 2012). It has been demonstrated that C. nodosa typically behaves as a 'light-plant', whereas C. prolifera behaves as a 'shade-plant', based on the differences in the way PAR is absorbed, the pigment composition, and the subsequent physiological mechanisms for dissipating excess light energy between the two macrophytes (Malta et al 2005, García-Sánchez et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation